THE ROLE OF ENTREPRENEURSHIP IN INCREASING THE INTEREST OF ISLAMIC ECONOMICS STUDENTS IN LOCAL FOOD PROCESSING PRODUCTS INDEPENDENT INNOVATION - Nur Aini; Ahmad Hulaimi; Suci Canda Ati; Veni Edrian; Gina Elfida (ITB AAS Indonesia Surakarta, 2025)
The research entitled the role of entrepreneurship in increasing the interest of Islamic economics students in local food products based on independent innovation, aims to analyze the role of entrepreneurship in increasing the interest of Islamic Economics students in local food products based on independent innovation. The location of the research in terms of theoretical learning was carried out in the area of ​​the University of Muhammadiyah Mataram Campus and its surroundings, including the Taman Udayana area as the center of student entrepreneurial activities. The method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation of students who are active in Student Activities in terms of entrepreneurship with students who collaborate with mothers who already have local food product brands. The results of the study show that the application of entrepreneurial values ​​such as innovation, creativity, and courage to take risks, significantly contribute to growing student interest in business. Bazaar activities, business training, and involvement in business incubator programs on campus also encourage the emergence of local food-based business ideas such as processed corn, cassava, and palm water or sweet palm wine. In addition, understanding the principles of Islamic economics provides an ethical foundation in their business practices. This study concludes that entrepreneurship plays an important role in shaping students' independent mindset and encouraging the development of sustainable and competitive local food products. Keywords: Entrepreneurship, Interest, Students, Products, Food